Medical education in Libya: Challenges, hopes, and recommendations - Arif Al-Areibi (Libyan International Medical University Journal)
The purpose of this review is to examine the current Libyan medical education system, look at its positive and negative aspects, and to provide suggestions and recommendations that could help improve the quality of the system today. The current Libyan medical education system has aged, and unfortunately, cannot meet both societal needs and the new requirements from the World Federation of Medical Education (WFME). The WFME issued a strong statement to all international medical schools to meet its new accreditation standards by 2023 in order for them to be recognized internationally. Lacking almost 70% of the international standards, Libyan medical schools will require considerable amount of time and resources to solve the issue. The process of changing and updating the system will involve all parts of the learning environment, including students, teachers, curriculums, resources, research, and governing bodies.